Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(2.5^2.3^2+\left\{\left[2.5^3-\left(5x+4\right).5\right]:\left(2^2.3.5\right)\right\}=453\)
\(2.25.9+\left\{\left[2.125-\left(5x+4\right).5\right]:\left(4.3.5\right)\right\}=453\)
\(50.9+\left\{\left[250-\left(5x+4\right).5\right]:60\right\}=453\)
\(450+\left\{\left[250-\left(5x+4\right).5\right]:60\right\}=453\)
\(\left[250-\left(5x+4\right).5\right]:60=453-450\)
\(\left[250-\left(5x+4\right).5\right]:60=3\)
\(250-\left(5x+4\right).5=3.60\)
\(250-\left(5x+4\right).5=180\)
\(\left(5x+4\right).5=250-180\)
\(\left(5x+4\right).5=70\)
\(5x+4=70:5\)
\(5x+4=14\)
\(5x=14-4\)
\(5x=10\)
\(x=10:5\)
\(x=2\)
Vậy \(x=2\)
b) \(\left|x-\frac{1}{3}\right|=2\)
\(\Rightarrow\orbr{\begin{cases}x-\frac{1}{3}=-2\\x-\frac{1}{3}=2\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=\left(-2\right)+\frac{1}{3}\\x=2+\frac{1}{3}\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=\frac{-5}{3}\\x=\frac{7}{3}\end{cases}}\)
Vậy \(x\in\left\{\frac{-5}{7};\frac{7}{3}\right\}\)
52x-3-2.52=52.3
52x-3-50=75
52x-3=75+50
52x-3=125
=>52x-3=53
=>2x-3=3
=>2x=6=>x=3
\(5^{2.x-3}-2.5^2=5^2.3\)
\(5^{2.x-3}-50=75\)
\(5^{2.x-3}=75+50\)
\(5^{2.x-3}=125\)
\(125=5^3\)
\(x=3\)
52x - 3 - 2.52 = 52.3
52x - 3 - 2.25 = 25.3
=> 52x : 53 = 75 + 50
=> 52x : 125 = 125
=> 52x = 125 .125
=> 52x = 1252
=> 52x = 56
=> 2x = 6
=> x = 6 : 2
=> x = 3
52.x-3 - 2 . 52 = 52 . 3
52.x-3 - 2 . 25 = 25 . 3
52.x-3 - 50 = 75
52.x-3 = 75 + 50
52.x-3 = 125
=> 52.x-3 = 53
=> 2 . x - 3 = 3
2 . x = 3 + 3
2 . x = 6
x = 6 : 2
x = 3
52x-3 - 2.52 = 52.3
52x-3 = 52.3 + 2.52
52x-3 = 52.(3 + 2)
52x-3 = 52.5 = 53
=> 2x - 3 = 3
=> 2x = 3 + 3
=> 2x = 6
=> x = 6 : 2
=> x = 3
Vậy x = 3
52x-3-2.52=52.3
52x-3-50=75
52x-3=125
52x-3 = 53
2x-3=3
2x=6
x=3
\(5^{2x-3}-2.5^2=5^2.3\)
\(5^{2x-3}-50=75\)
=>\(5^{2x-3}=75+50=125\)
Mà \(5^{2x-3}=125=5^3\)
=>2x-3=3
2x=3+3=6
=>x=3
-52x-32.52=52.3
\(5^{2x-3}\)-50=75
\(5^{2x-3}\)=75+50
\(5^{2x-3}\)=215
\(5^{2x-3}\) =\(5^3\)
\(\Rightarrow\) \(2x-3=3\)
\(2x=3+3\)
\(2x=6\)
\(x=6:2\)
\(x=3\)
Vậy x = 3
\(5^{2x-3}-2.5^2=5^2.3\)
\(5^{2x-3}-50=75\)
\(5^{2x-3}=75+50\)
\(5^{2x-3}=125=5^3\)
\(\Rightarrow2x-3=3\)
\(2x=3+3=6\)
\(x=6:2=3\)
\(5^{2x}:5^3=5^2.3+2.5^2\)
\(5^{2x}:5^3=5^2.\left(3+2\right)\)
\(5^{2x}:5^3=5^2.5\)
\(5^{2x}:5^3=5^3\)
\(5^{2x}=5^3.5^3\)
\(5^{2x}=5^6\)
\(\Rightarrow2x=6\)
\(x=6:2\)
\(x=3\)